Host–plant relationships and natural enemies of the invasive mealybug, Rastrococcus iceryoides Green in Kenya and Tanzania. (16th December 2015) - Tanga, C. M.; Ekesi, S.; Govender, P.; Mohamed, S. A.
Abstract: The invasive mango mealybug, Rastrococcus iceryoides Green (Hemiptera: Pseudococcidae), believed to be native to southern Asia has rapidly invaded Kenya and Tanzania. A survey was carried out from February 2008 to July 2009 to study its geographical distribution, host–plant relationships and associated parasitoids in both countries. Our results infer that R. iceryoides is widely distributed across the coastal belts of both countries. Rastrococcus iceryoides was recorded from 29 cultivated and wild host plants from 16 families. Twenty‐one of these host plants are new records. Among the cultivated host plants, M. indica (407.68 ± 9.26/twig and 75.68 ± 7.13/leaf in Kibaha, and 595.86 ± 17.2/fruit in Kinondoni) and Cajanus cajan (L.) Millspaugh (18.15 ± 4.22/leaf and 233.62 ± 18.9/twig in Morogoro) recorded the highest levels of infestation. Parkinsonia aculeata (394.62 ± 11.7/twig, 0.15 ± 0.03/leaf and 8.44 ± 0.94/fruit in Kinango), Caesalpinia sepiaria Roxb. (3.33 ± 0.76/leaf and 155.81 ± 9.16/twig in Kinondoni) and Deinbollia borbonica Scheff. (2.70 ± 0.66/leaf and 112.65 ± 5.3/twig in Kibaha) were found to be the most heavily infested wild host plants. Six parasitoid species were recovered and are reported here for the first time to parasitize R. iceryoides . Anagyrus pseudococci Girault was the most dominant species accounting for 21% parasitism on M. indica and 20% parasitism on P. aculeata in Tanzania and Kenya, respectively. Despite this, the ability of the parasitoid to regulate the population of R. iceryoides was inadequate. Therefore, there is a need for foreign exploration and introduction of efficient coevolved natural enemies from its aboriginal home of southern Asia to minimize its impact on horticulture in Africa.